1. Ilímaussite, a new rare Earth-Niobium-Barium Silicate from Ilímuassaq, South Greenland. - Semenov, E. I.; Kazakova, M. E.; Bukin, V. J. (Meddelelser om Grønland, 1968)
A new mineral – Na4Ba2CeFeNb2Si8O28.5H2O - found in a hydrothermal vein in nepheline-sodalite syenite (naujaite) of the Ilímaussaq alkaline massif is described. The mineral is named ilimaussite after the locality where it was found. It forms brownish-yellow lamellae and is associated with ussingite, chkalovite and epistolite. The specific gravity is 3.6. The mineral is optically uniaxial positive; ne = 1.695, n0 = 1.689. The mineral is hexagonal, ao = 10.80, co = 20.31, Vo = 2052 Å3, Z = 3. The chemical composition is : SiO2 - 31.28, TiO2 - 1.64, Nb2O5 - 13.20, TR2O3 - 10.60, Fe2O3 - 3.18, BaO - 23.62, Na2O - 7.00, K2O - 3.80, loss by ignition - 6.43 ; total 100.75.